ON THE FISHING EXPERIMENTS CONDUCTED WITH A 10 FT. BEAM-TRAWL NET - Deshpande, S D (Indian Journal of Fisheries, 2015)
Although the origin.and history are not known, beam-trawl is an efficient fishing" gear for bottom dwellers particularly shrimps. The net can be efficiently operated both from a sailing craft and a mechanised boat. This characteristic feature renders it as a possible "connecting link" between mechanised modern trawls on the one hand and similar towed gear from sailing crafts on the other. Beam-trawls and the Uke had been the initial step in many countries, where modern forms of trawl have come to stay. Scofield (1948) dates the origin of a similar fishing net on the Atlantic Coast over 500 years back and further indicates that the gear is still in vogue. In the countries like Thailand, Philippines and Japan, Beam-trawl still maintains its popularity for shrimp fishing.